2019
DOI: 10.1093/aje/kwz101
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Speed of Multimorbidity Accumulation in Old Age and Life Experiences: A Cohort Study

Abstract: Rapidly accumulating multiple chronic conditions (multimorbidity) during aging are associated with many adverse outcomes. We explored the association between 4 experiences throughout life—childhood socioeconomic circumstances, early-adulthood education, midlife occupational stress, and late-life social network—and the speed of chronic disease accumulation. We followed 2,589 individuals aged ≥60 years from the Swedish National Study on Aging and Care in Kungsholmen for 9 years (2001–2013). Information on life e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 60 publications
4
36
0
1
Order By: Relevance
“…In the mediation analyses, demand-control status was treated as an ordinal variable according to the magnitude of the associations between demand-control combinations and the annual change in total disability (i.e., the slopes shown in Figure 10), that is, the detrimental effects of demand-control categories followed an order from the lowest to the highest: active jobs, high strain, low strain, and passive jobs. Such dose-response pattern was also seen in the changes in MMSE score (Figure 6-A) and number of chronic diseases over time (95) in relation to these job categories. The mediation analyses revealed that 38.5% of the total association between demand-control status and disability trajectories was mediated by the decline in cognitive function, while 18.4% was mediated by the accumulation of medical conditions that occurred during the follow-up period (Figure 11).…”
Section: The Mediating Role Of Changes In Cognitive Function and Chrosupporting
confidence: 53%
“…In the mediation analyses, demand-control status was treated as an ordinal variable according to the magnitude of the associations between demand-control combinations and the annual change in total disability (i.e., the slopes shown in Figure 10), that is, the detrimental effects of demand-control categories followed an order from the lowest to the highest: active jobs, high strain, low strain, and passive jobs. Such dose-response pattern was also seen in the changes in MMSE score (Figure 6-A) and number of chronic diseases over time (95) in relation to these job categories. The mediation analyses revealed that 38.5% of the total association between demand-control status and disability trajectories was mediated by the decline in cognitive function, while 18.4% was mediated by the accumulation of medical conditions that occurred during the follow-up period (Figure 11).…”
Section: The Mediating Role Of Changes In Cognitive Function and Chrosupporting
confidence: 53%
“…The modelling strategy was sequential, including additional variables and complexity. Dekhtyar et al (2019) Multimorbidity (chronic disease accumulation)…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for choosing a specific list of diseases was usually described. For example, some studies explained that they included chronic diseases with high prevalence and high risk of disability and mortality (Fabbri et al, 2015;Fabbri et al, 2016) and others included diseases that were assessed and validated by clinical consensus (Calderon-Larranaga et al, 2019;Calderón-Larrañaga et al, 2018;Dekhtyar et al, 2019;Perez et al, 2019;Strauss et al, 2014). Some studies included diseases based on the common Charlson and Elixhauser multimorbidity indices (Fraccaro et al, 2016;Gellert et al, 2018;Hanson et al, 2015;Hiyoshi et al, 2017;Kim et al, 2018;Lindhagen et al, 2015;Zeng et al, 2014) but lists were sometimes adapted, either by augmenting with extra (perceived relevant) conditions (Hiyoshi et al, 2017) or by removing diseases due to data sensitivity restrictions (Fraccaro et al, 2016).…”
Section: Diseases Included In Multimorbidity Measuresmentioning
confidence: 99%
“…Thus, passive jobs can also lead to chronic stress. Passive jobs have previously been demonstrated to be associated with disability, multimorbidity and other outcomes (41,42).…”
Section: Discussionmentioning
confidence: 99%